Studies on the Protozoan Parasites of Hilsa Shad, Tenualosa Ilisha in Bangladesh (Bangladesh Journal of Zoology, 2012)
Present investigation was conducted to study the protozoan parasites of    hilsa shad, Tenualosa ilisha collected from Aricha Ghat, Dhaka. Thirty fishes were observed. Fishes were collected during months of August 2010 and September 2010. A total of 1099 individuals of protozoan parasite of eight genera/species were recorded during the present study. These parasites were found on body surface, gills and gall bladder of the fish. Jirovecia piscicola had the highest prevalence (53.33%) while Coccomyxa baleswarensis had the lowest prevalence (26.67%) of infection. Most of the host individuals had double (43%) and single (40%) species infection. Only a few (10%) host had triple species infection. No fish had more than three species of parasite at a time. Glugea sp. dominated over all other parasites. J. piscicola, Zschokkella ilishae and Ceratomyxa hilsae had almost  similar abundance while C. baleswarensis had the lowest (5.64%) abundance. Abundance of Sphaeromyxa dighae, Myxobolus sp. and Kudoa sp. were comparatively low ranging from 9.36% to 17.35%. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12892 Bangladesh J. Zool. 40(1): 33-41, 2012